2017
DOI: 10.3354/meps12297
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tracking and stable isotope analysis highlight differential recruitment among foraging areas in green turtles

Abstract: Identifying links between breeding and non-breeding sites in migratory animals is an important step in understanding their ecology. Recognising the relative importance of foraging areas and ascertaining site-specific levels of recruitment can provide fundamental and applied insights. Here, satellite telemetry and the stable isotope ratios (δ 13 C, δ 15 N and δ 34 S) of 230 green turtles Chelonia mydas from a regionally important rookery in northern Cyprus were employed to evaluate the relative importance of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 91 publications
(120 reference statements)
3
64
0
Order By: Relevance
“…Finally, no telemetry data have been published regarding the foraging areas used by the turtles nesting in Akamas, although our results suggest that the Israeli coast is not one of them. Considering published data and our own results, it seems that there might be a contradiction, as stable isotope analysis suggested that a significant proportion of turtles (39%) from Alagadi approach the Israeli coast on the migration to Egypt (Bradshaw et al, ), but this was not detected when performing an MSA (present study).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Finally, no telemetry data have been published regarding the foraging areas used by the turtles nesting in Akamas, although our results suggest that the Israeli coast is not one of them. Considering published data and our own results, it seems that there might be a contradiction, as stable isotope analysis suggested that a significant proportion of turtles (39%) from Alagadi approach the Israeli coast on the migration to Egypt (Bradshaw et al, ), but this was not detected when performing an MSA (present study).…”
Section: Discussionmentioning
confidence: 43%
“…Our results demonstrate that a significant proportion of Turkish individuals follow the Levantine coast and arrive in Israeli foraging areas. Additional studies incorporating stable isotopes are desirable to fully understand the habitat use of Turkish nesting turtles (Bradshaw et al, ). Five animals from Israel, three females and two males, were also recently tracked by telemetry showing that Israeli turtles remain in the vicinity of this area, and thus explaining why they were detected among the stranding animals (Levy et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If isotope ratios of foraging grounds are distinct, this enables untracked females to be reliably assigned to putative foraging grounds from a single tissue sample, hence providing an understanding of the spatial ecology at a population level (e.g., Ceriani et al, ; Seminoff et al, ). In addition, the temporal consistency of isotope ratios has been used for confirming foraging ground fidelity in marine taxa (e.g., Newsome et al, ), including marine turtles (e.g., Bradshaw et al, ; Thomson et al, ). If foraging ground fidelity occurs, then long‐term studies enable the proportion of individuals in each annual nesting cohort using each foraging ground to be determined across multiple nesting seasons and therefore identifying potential shifts in population dynamics (e.g., Bradshaw et al, ; Ceriani et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the temporal consistency of isotope ratios has been used for confirming foraging ground fidelity in marine taxa (e.g., Newsome et al, ), including marine turtles (e.g., Bradshaw et al, ; Thomson et al, ). If foraging ground fidelity occurs, then long‐term studies enable the proportion of individuals in each annual nesting cohort using each foraging ground to be determined across multiple nesting seasons and therefore identifying potential shifts in population dynamics (e.g., Bradshaw et al, ; Ceriani et al, , ). Temporal changes in the proportion of individuals using each foraging ground could be inferred as changes in the foraging ground dynamics, including changes in recruitment, survival of individuals or changes in foraging resources and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%